Універсальні та національні прецедентні феномени у заголовках українських медійних видань - Петренко, А. (Культура слова, 2019)
Стаття присвячена аналізові прецедентних феноменів, що функціонують у сучасному масмедійному дискурсі. Зосереджено увагу на вивченні національно-культурної маркованості прецедентних феноменів, описано класифікації прецедентних феноменів на основі їх функціонування в різних за обсягом національно-мовних та соціальних групах. Запропоновано авторський підхід до визначення національної маркованості прецедентних феноменів. Залучення методики асоціативного експерименту дало змогу виявити ступінь знання мовцями національно-прецедентних феноменів української лінгвокультури, а також визначити їхні ознаки як ментефактів, що формують національну когнітивну базу сучасних українців. Modern mass communication has become the lingual background of the definition of linguistic preferences of «human speaker» (Homo Loquens). Nowadays, media discourse is not only an information source, but also a means of influence that can manipulate different human moods, feelings, preferences, including those at the level of consciousness and language. Most scholars of contemporary journalistic discourse point to two parallel trends. On the one hand, the language of mass communication tends to individualize the linguistic expression of information, on the other – to the traditional, standard, cliché, etc. One of the means of penetrating the human consciousness and activating its thinking activity is the use of precedent phenomena that can reveal both tendencies at the same time. The precedent phenomena, having fallen into the field of view of scholars at the end of the twentieth century, continue to hold the interest of researchers in various fields of humanities. Everything related to the study of mentality, issues of the interconnection of language and thinking, prompts new and new research. This explains the numerous works of Ukrainian linguists, whose subject of analysis are the precedent phenomena in different aspects of their expression by the means of different languages in different genres and different discursive practices. In particular, these are publications by F. S. Batsevych, Yu. M. Velikoroda, I. O. Golubovska, O. A. Gapchenko, S. Ya. Yermolenko, S. S. Yermolenko, E. A. Karpilovska, T. Yu. Kalchenko, O. Yu. Karpenko, A. K. Moisienko, E. S. Otin, O. O. Selivanova, N. V, Listen, M. I. Stepanenko, G. M. Sіuta, T. V. Radzievska, I. A. Kazimirova, S. B. Serebrova, G. Yu. Kasim, T. V. Chrdileli, T. А. Cosmeda, O. A. Levchenko, O. G. Ruda, I. V. Bogdanov, R. S. Chornovol-Tkachenko, S. V. Lazarenko, O. O. Malenko, N. O. Sunko, O. V. Nadyuk, O. S. Palchevska, L. Y. Mercoton, M. V. Mamich, O. B. Sprissa, A. A. Berestova, G. V. Tashchenko, M. V. Roslitskaya and others. The purpose of this article is to describe national and universal precedent phenomena in the media resources of Ukraine, to clarify their significance for contemporary speakers. Its relevance is determined by the need to identify the main features of the national cognitive base of modern Ukrainian.